Performance comparative study of dual-permanent-magnet vernier machines with different topologies - Chia, Ting Hong (Nanyang Technological University, 2023)
Permanent magnet vernier machines (PMVM) mostly used in heavy industry. These machines can emit excessive torques with minimum speeds. In past years several PMVM novel topologies were proposed by various groups for special duties. Changing rotor magnet structure, stator structure, and materials and adding various magnet effects are the key things behind all of these different kinds of PMVM topologies. Some machine architectures were presented with dual rotors and stators. Mostly these PMVM machines are very applicable to electric vehicles. These PMVM machines are very reliable than other types of motor devices because PMVM is operating with the magnetic gearing effect principle. However, these motors are very expensive to comparing other motors because of their higher efficiency, lower noise, and other features. In the past decade, engineers tempted to develop PMVM machines with magnetic flux barriers which are very helpful to improve the electromagnetic performances of the device. Likewise, in this paper, a new flux barrier PMVM was designed as a JMAG designer simulation called Flux Barrier tapered U-shaped permanent magnet vernier machine (FBU-PMV). And then most of its electromagnetic performances were analyzed such as Torque, back-EMF, air-gap flux density, power factor, and so on. 25% fewer materials were used for this machine structure. Besides a brief feature comparison of existing PMVM topologies was presented in this paper. All the above-mentioned motor features were discussed for those PMVM topologies. JMAG-designed FBU machine simulation performed well. However, some rated values for some features were altered. This FBU-PMV is a newly designed single side PMV machine. A tapered “U” shaped permanent magnet mechanical architecture was rendered as rotor structure.